Key impact of phase dynamics and diamagnetic drive on Reynolds stress in magnetic fusion plasmas. (7th May 2021) - Sarazin, Y; Dif-Pradalier, G; Garbet, X; Ghendrih, P; Berger, A; Gillot, C; Grandgirard, V; Obrejan, K; Varennes, R; Vermare, L; Cartier-Michaud, T
Abstract: Reynolds stress is a key facet of turbulence self-organization. In the magnetized plasmas of controlled fusion devices, the zonal flows that are driven by the averaged Reynolds stress modify the confinement performance. We address this problem with full- f gyrokinetic simulations of ion temperature gradient-driven turbulence. From the detailed analysis of the three-dimensional electric potential and transverse pressure fields, we show that the diamagnetic contribution to the Reynolds stress—stemming from finite Larmor radius effects—exceeds the electrostatic contribution by a factor of about two. Both contributions are in phase, indicating that pressure does not behave as a passive scalar. In addition, the Reynolds stress induced by the electric drift velocity is found to be mainly governed by the gradient of the phase of the electric potential modes rather than by their magnitude. By decoupling Reynolds stress drive and turbulence intensity, this property indicates that a careful analysis of phase dynamics is crucial in the interpretation of experiments and simulations.